Taxonomy of imperative in religious discourse - Malysheva , Maryna (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article is devoted to religious discourse, which is the most specific and complex manifestation of communication units, in which linguistic laws operate according to semantic significance and pragmatically reflect unconventional correlations between morphological and syntactic grammatical categories; critical evaluation of linguopragmatic discursive theoretical studies was carried out; the questions of the modal correlation of reality and assertion in linguistics are covered; imperative as a grammatical category of the verb hasn’t only a predicative character, but also a modal which in religious discourse is represented by an opposite vector of functioning, in comparison with the classical modal split according to the types of relation to reality and modal values ​​through the prism of the category of “speaker’s sight”; it is emphasized that the pragmatism of the referencing mechanism in combination with the logical-philosophical approach to understanding the imperative shades of modality are the main means of their functional-semantic analysis and definition in religious discourse; it’s noted that in religious discourse modality is based on the own plot structure of the institution, which is expressed through the pragmatic goal and it’s imperative realization, which ideally creates God and passes through the preacher to the addressee; modal shades of the ordering method in the religious environment are defined; imperative modal shades are differentiated according to the logical and intuitive perception of the religious texts of the researcher due to the force of evading the desired action by the addressee; the religious taxonomy of the imperative based on the principle of physical dispersion of light on the 7 basic spectra is created (order, prohibition, prompt, request, exhort, caveat, prevent, advice, wishes), the combination of which is formed by the strongest core imperative – an order (the least desirable for the fulfillment of the imperative action in greetings , and the biggest one - in prohibition); the absence of the notion of “order” in religious discourse is substantiated; peripheral imperative spectra provided a conceptual essence.